2020
DOI: 10.1371/journal.pone.0237797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of window-to-wall-area ratio on thermal performance of building wall materials in Elazığ, Turkey

Abstract: In this study, the effect of glazing-to-total-wall-area ratio on the thermal performance of different wall materials is numerically investigated in terms of heat transmission load. The investigation was performed for a South-facing wall in Elazığ, Turkey. The heat transmission load through walls and windows are determined separately for summer and winter climate conditions. In this analysis, the frame area of the window is not considered. Therefore, whereas the glazing area on uninsulated and insulated walls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(44 reference statements)
2
6
0
Order By: Relevance
“…5), thus an increase in the wall area would result in an increase in solar gains into the building and then an increase in the energy demand for cooling. These results are consistent with the findings in Ozel and Ozel's [13] research in Turkey. In the research [13] it was observed that the glazing area of the AAC wall can be made larger for both summer and winter conditions when the wall was not insulated; while for the insulated wall, the wall material did not have any significant effect on the glazing area.…”
Section: Relationship Between the Wall Materials And Window-to-wall R...supporting
confidence: 93%
See 3 more Smart Citations
“…5), thus an increase in the wall area would result in an increase in solar gains into the building and then an increase in the energy demand for cooling. These results are consistent with the findings in Ozel and Ozel's [13] research in Turkey. In the research [13] it was observed that the glazing area of the AAC wall can be made larger for both summer and winter conditions when the wall was not insulated; while for the insulated wall, the wall material did not have any significant effect on the glazing area.…”
Section: Relationship Between the Wall Materials And Window-to-wall R...supporting
confidence: 93%
“…These results are consistent with the findings in Ozel and Ozel's [13] research in Turkey. In the research [13] it was observed that the glazing area of the AAC wall can be made larger for both summer and winter conditions when the wall was not insulated; while for the insulated wall, the wall material did not have any significant effect on the glazing area. However, these findings differ from the results in the research carried out by Sene et al in 2017.…”
Section: Relationship Between the Wall Materials And Window-to-wall R...supporting
confidence: 93%
See 2 more Smart Citations
“…Windows and other similar installations enable the usage of sunlight to minimize artificial lighting and improve indoor aesthetics. Yet, solar radiation through windows is responsible for 40–70% of the cooling load in buildings …”
Section: Introductionmentioning
confidence: 99%